ANALISIS PENDAPATAN PETERNAK DARI USAHA BUDIDAYA TERNAK JANGKRIK (Studi Kasus pada Peternakan Padli di Kota Denpasar) - A., Novendra; Sukanata, I W.; Budiarta, I W. (Jurnal Peternakan Tropika; Vol 4 No 2 (2016), 2016)
This study aims to determine the farmer income, costs structure, R/C Ratio, and the breakeven point of the crickets production. the research was conducted in Padli’s farm at the Pondok Indah 1 road no. 9X, Denpasar city. This research has been carried out since january 2016 to april 2016. Primary data were used in this study than collected by interview and observation. Cost structure, income, R/C Ratio and break even were determined by quantitative methode.This study has shown that acceptance of farming crickets Rp. 6.300.000 and the cost  of cultivation of crickets farm consist of investment costs and operating costs. The cost of investment for growing of 1.200 gram scale of crickets egg were Rp.3.450.000,-. Total operating expenses amounted to Rp. 2.411.500 consists of fixed costs of 43,81 % and variabel costs of 56,19 %. Farmer income derived from this farm is Rp.3.888.500,- per period, R/C ratio of these farm is about to 2,61. Break even point is reached when the crickets selling price Rp.11.483,33,- per kg, or when the farm produce of crickets about 44,86 kg/period. Management of livestock farming cricket are good enough that involves several aspects, among other: feed management and pest and disease management.
Keywords: Cricket,Revenues, R/C ratios, break even.